2002
DOI: 10.1039/b206554a
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to selectivity in the Zn(ii)–phthalocyanine-photosensitized inactivation of wild-type and antibiotic-resistant Staphylococcus aureus

Abstract: A number of Zn(II)- phthalocyanines bearing peripheral substituents of cationic nature due to the presence of quaternarized anilinium or ammonium groups were shown to be efficient photoantimicrobial agents: a 4-5 log decrease in the survival of both wild-type or methicillin-resistant Staphylococcus aureus was obtained upon short irradiation times in the presence of phthalocyanine concentrations as low as 0.1 microM. A careful selection of the experimental protocol, and in particular the use of short (5 min) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 23 publications
0
72
0
Order By: Relevance
“…There is a permeable outer peptidoglycan layer in Gram-positive bacteria, which enables the penetration of photosensitive substance to the cytoplasmatic membrane, the target of PACT. Thickening of the cell wall of MRSA (methicilin-resistant Staphylococcus aureus) or VRE (vancomycin-resistant enterococci) diminishes the penetration of antibiotics, antiseptics and disinfectants, however, the decrease in effectiveness of PACT has not been proved so far [18]. The wall of Gram- negative bacteria is more complex.…”
Section: Target Microorganismsmentioning
confidence: 99%
“…There is a permeable outer peptidoglycan layer in Gram-positive bacteria, which enables the penetration of photosensitive substance to the cytoplasmatic membrane, the target of PACT. Thickening of the cell wall of MRSA (methicilin-resistant Staphylococcus aureus) or VRE (vancomycin-resistant enterococci) diminishes the penetration of antibiotics, antiseptics and disinfectants, however, the decrease in effectiveness of PACT has not been proved so far [18]. The wall of Gram- negative bacteria is more complex.…”
Section: Target Microorganismsmentioning
confidence: 99%
“…In the last decade, cationic porphyrins (2,23,24), phthalocyanines (26,27,37), and chlorins (12) have gained popularity as antimicrobial photosensitizers due to their abilities to inactivate both gram-positive and gram-negative bacteria. This has fueled the thought that these photosensitizers could be successfully applied as broadband antimicrobial agents.…”
mentioning
confidence: 99%
“…ZnPc predominantly gener- [54]. Native ZnPc was found to be ineffective against Gramnegative bacteria such as E.coli [48] and had to be applied in combination with membrane perturbing agents such as ethylenediaminetetraacetic acid (EDTA) or calcium chloride to ensure (intra)cellular delivery [23,55,56]. In contrast, ZnPc exhibited affinity for the Gram-positive Streptococcus mitis, which involved the association with membrane proteins residing in the cytoplasmic membrane [49,54].…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…Furthermore, the tertiary ammonium-substituted methylene blue derivative possesses lower pK a values than the lower-order substituents, which results in faster deprotonation when bound to the negatively charged bacterial cell envelope structure and better uptake. It was further shown that, by employing relatively short drug-light intervals, APDT of the infected area killed the photosensitized bacteria without damaging the surrounding healthy cells/tissues [22][23][24]. Phenothiazinium is also a substrate for multidrug resistance pumps [25,26], a family of transmembrane proteins that mediate the efflux of amphipathic cations, amongst others.…”
Section: Phenothiaziniumsmentioning
confidence: 99%